First in-beam experiment with the ELIADE detectors: a spectroscopic study of 130La. (2nd December 2021) - Capponi, L.; Kuşoğlu, A.; Söderström, P.-A.; Balabanski, D.L.; Turturică, G.V.; Bocchi, G.; Chesnevskaya, S.; Dhal, A.; Dinescu, D.; Djourelov, N.; Niu, Y.; Oprisa, A.; et al.
Abstract: The new facility, Extreme Light Infrastructure – Nuclear Physics (ELI-NP), is a combined laser-gamma nuclear physics research facility currently undergoing its final implementation stages in Măgurele near Bucharest, Romania. It already hosts two fully-operational 10 PW laser arms and, by 2023, it will also house a γ-beam system based on laser Compton backscattering, capable of delivering a high-brilliance, low-energy beam at E γ ≲ 19.5 MeV. Owing to this unique laser-gamma instrumentation combination, several types of experiments will be possible at ELI-NP, including high precision nuclear resonance fluorescence (NRF) experiments. In this case, the main γ-beam detection system for performing NRF studies at ELI-NP is represented by the ELI Array of DEtectors (ELIADE), featuring eight high-purity germanium (HPGe) segmented clover detectors. The current work presents the characteristics of two of the ELIADE detectors, including their photopeak detection efficiency, energy resolution, and peak-to-total ratio measured using γ-ray sources, as well as the timing performance obtained via in-beam measurements. For these latter detector tests, 130 La was populated via the fusion evaporation reaction 121 Sb( 12 C, 3n) 130 La using a beam energy of 53 MeV at the Horia Hulubei National Institute of Physics and Nuclear Engineering (IFIN-HH), also located in Măgurele. Herein, we report on the results of the ^130La linear polarization measurements taken using the ELIADE detectors as Compton polarimeters. The results obtained from the in-beam experiment were compared to several already published works and we present new information on the transition multipolarity in 130 La.